A comparative study of diffraction methods for strain measurement in a particulate MMC - Korsunsky, A; Wells, K; Shaw, B (Trans Tech Publ, 2000)
Diffraction strain measurement techniques offer a unique analytical tool to the materials scientist and engineer, interested in the residual and live stresses in engineering materials and components. The present paper reviews the application of several experimental techniques to the study of internal stress development in an Al/SiC particulate composite. A comparison is made between using laboratory X-ray diffraction with a stress camera; synchrotron X-ray diffraction using a high resolution spectrometer, and a 2D detector; and neutron diffraction using a reactor, and a pulsed spallation source. The performance of various instruments is compared in terms of a semi-qualitative parameter describing time required for data collection. The capabilities and shortcomings of each method are highlighted. Possible ways of achieving complementarity of results from different instruments are discussed.